2013
DOI: 10.1177/0276146713500307
|View full text |Cite
|
Sign up to set email alerts
|

Linking Subsistence Activities to Global Marketing Systems

Abstract: This article aims to improve the understanding of how micro-level subsistence activities might be related to higher-level phenomena to increase well-being of individuals and communities in contexts characterized by institutional gaps. Using coffee as illustrative case, it explores the link between local entrepreneurial activities in developing countries and global marketing systems, with specific attention to the role of institutions. In this way, the article also sheds some light on broader research challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…In the same DRC setting, coffee has emerged in recent years, specifically in the Eastern provinces of North and South Kivu bordering Rwanda, an area characterized by a vicious cycle of conflict and violence, poverty and poor governance. Coffee projects for small farmers have been shown in other countries to help fill institutional gaps by creating 'compensatory structures', including new/different networks, intermediary entities and partnerships, while also generating positive outcomes for farmers and their communities (Kolk, 2014a). Our research in Eastern DRC and Rwanda showed that transformative partnerships are more common in the local coffee sector than amongst the (predominantly mining) multinationals active in the DRC.…”
Section: Partnerships At Different Levels Local Levelmentioning
confidence: 67%
See 1 more Smart Citation
“…In the same DRC setting, coffee has emerged in recent years, specifically in the Eastern provinces of North and South Kivu bordering Rwanda, an area characterized by a vicious cycle of conflict and violence, poverty and poor governance. Coffee projects for small farmers have been shown in other countries to help fill institutional gaps by creating 'compensatory structures', including new/different networks, intermediary entities and partnerships, while also generating positive outcomes for farmers and their communities (Kolk, 2014a). Our research in Eastern DRC and Rwanda showed that transformative partnerships are more common in the local coffee sector than amongst the (predominantly mining) multinationals active in the DRC.…”
Section: Partnerships At Different Levels Local Levelmentioning
confidence: 67%
“…So-called 'institutional voids' have received attention in the business literature, mostly in conceptual work (e.g. Khanna & Palepu, 1997;Tracey & Phillips, 2011), and in a few exploratory qualitative studies (Kolk, 2014a;Mair & Martí, 2009;Mair, Martí, & Ventresca, 2012). This aspect deserves further attention for fragile states, which seem to exemplify an 'extreme', unconventional and under-researched context (Bamberger, 2008;Bamberger & Pratt, 2010).…”
Section: Identifying Missing Links Introductionmentioning
confidence: 99%
“…Particularly in developing countries characterized by institutional voids or gaps, the potential contribution of market actors to alleviate poverty has been studied in different literatures. Examples include bodies of work on subsistence marketplaces, bottom of the pyramid, cross-sector partnerships for sustainable development, and social entrepreneurship (Bacq & Janssen, 2011;Kolk, 2014;McKague & Oliver, 2012;Rivera-Santos, Rufín, & Kolk, 2012;Valente & Crane, 2010).…”
Section: Hybrid Organizations In Their Contextmentioning
confidence: 99%
“…We focused on organizations with international linkages, as these are vital for the economic and social development of local farmers, their families, and communities (Kolk, 2014;Mutandwa et al, 2009); they also generate the most interesting insights for practitioners outside the specific context of our study. To obtain insight into the range and type of actors involved in the coffee sector in the Kivu region, we first made an inventory of all organizations present--firms, cooperatives, and nongovernmental organizations (NGOs)--through various databases (from organizations such as Fair Trade and the International Coffee Organization), the Internet, and NGO contacts (facilitated by the fact that the second author has long worked for an NGO and has ample experience in the region).…”
Section: Hybrid Organizations In Their Contextmentioning
confidence: 99%
“…The farmers' difficulties were widely reported in the media and academic literature, generating increased scrutiny to high profile brands and prompting Non-Government Organisations (NGOs) and consumer advocates to press for the adoption of farmer support programs [11,[16][17][18], among many others). Many of these brands shared these objectives and began their path to sustainability of their supply chain through different certification schemes that provided them with additional differentiation attributes and reduced their reputational risks [1,8,14,[19][20][21][22].…”
Section: The Evolving Voluntary Sustainability Standards Landscapementioning
confidence: 99%